Redescription of Brachycepsis Brendel, notes on Taphroscydmus Casey, and brief review of Nearctic genera of Stenichnini (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2021)
Stenichnini of the Nearctic region include twelve genera, of which two are cosmopolitan, two Holarctic, and eight are known only in North America. Morphological structures and taxonomic placement of most of them have been subjects of recent studies, with exception of Brachycepsis Brendel and Taphroscydmus Casey. Because the depository of the type material of the type species of Brachycepsis, B. fuchsii Brendel, remains unknown, Brachycepsis is redescribed and its diagnosis is emended based on examination of B. pacifica Casey. Although similar to Stenichnus Thomson and Parascydmus Casey, Brachycepsis shows unique characters that justify its separate placement. The depository of the type material of the sole species included in Taphroscydmus also remains unknown, and no other specimens that can be unambiguously attributed to this genus are available. Comparisons of the original description and subsequent redescriptions by Mannerheim and Casey reveals that the latter authors might have dealt with misidentified specimens. The true identity of Taphroscydmus remains unclear (although it may be identical with Brachycepsis), and it is currently not possible to unambiguously identify this genus. All Nearctic genera of Stenichnini are briefly reviewed, with characters important for identification discussed. An identification key to Nearctic genera (excluding Taphroscydmus) is given.